After Garissa : Kenya Revises Its Security Strategy to Counter al-Shabaab s Shifting Tactics - McGregor, Andrew
Al-Shabaab s April 2 attack on Kenya s Garissa University College that killed 147 non-Muslim students was the latest installment in al-Shabaab s campaign to force Nairobi to order a withdrawal of the Kenyan Defense Force (KDF) from the Jubaland region of southern Somalia. So far, the Kenyan government has presented an uncoordinated response that has largely focused on Islamist militancy as a foreign problem that is being imported (along with hundreds of thousands of unwanted refugees) across Kenya s porous border with neighboring Somalia.
Keywords: Al-Shabaab; Estrategias de seguridad; Kenia